PELAKSANAAN FUNGSI PEREKAM MEDIS TERHADAP PENYELENGGARAAN REKAM MEDIS DI PUSKESMAS PLERET BANTUL - , HANUM PUTRI C, Nuryati, A.Md., S.Far., MPH. ([Yogyakarta] : Universitas Gadjah Mada, 2014)
Backgrounds: Dinkes Bantul in 2011-2015 has a vision of \"health professional drivers of development towards a healthy society, independent, and fair quality\". To realize this vision, one of mission that built is to strive for equitable distribution of resources and the availability of quality health care with the goal of increasing need for health personnel suitably qualified / competence, health resources and health financing sufficient to increase the health status of the community. Based on preliminary study, it is known that Puskesmas Pleret Bantul is the only one parent Puskesmas in district Pleret. With the development of the Puskesmas, since 2009 a professional medical record officer placed in the medical record unit. However, although there has been a professional medical record officer that graduate from Diploma of Medical Record, not all medical record implementation is done by this professional medical record officer. Coding and inpatient admission is performed by nurses. Meanwhile, according to Permenkes 55 In 2013, medical record management must be carried out by the professional medical record officer. Moreover previous studies examining the role and function of the medical record officer in hospital, while in the Puskesmas medical record officer function has not been done. Objectives: This study aims to know the implementation of medical record officer in Medical Record Installation Puskesmas Pleret Bantul Methods: The type of research used in this study is descriptive qualitative with phenomenological approach. An interview guide and checklist were used as instrument for interview and observation. Results: Implementation of functions in the medical record management in Puskesmas Pleret Bantul is done by three TU officers and a professional medical record officer . The function of this professional medical record officer according to Permenkes 55 in 2013 has not been fully implemented. While the activities that is done by professional medical record officer to reaches its credit, there are 20 items of activities. Obstacles in the implementation of medical record officer function is in filing and report activities. Efforts of medical records officer have not been able to overcome the obstacles related their functions in Puskesmas Pleret Bantul.